2019
DOI: 10.1029/2018jd029521
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of Turbulent Energy Dissipation Rate From the VHF Radar and Radiosonde Observations in the Antarctic

Abstract: This study estimated the turbulent kinetic energy dissipation rates (TKEDRs) from 1‐year observations of the Program of the Antarctic Syowa Mesosphere‐Stratosphere‐Troposphere/Incoherent Scatter radar (PANSY radar) from October 2015 to September 2016 and compared the results with estimates from radiosonde measurements based on Thorpe's method. The radar‐based estimates showed that the TKEDR at Syowa Station was on the order of 10−5–10−3 m2/s3 in the altitude range of 1.5–19 km. Taking the proportional constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 99 publications
(160 reference statements)
5
37
1
Order By: Relevance
“…The strongest turbulence below the tropopause is also seen from individual profiles as well, which will be demonstrated in Figure 11a. The height of the maximum ε in the current study is different from some previous studies using radar data (e.g., Nastrom & Eaton, 1997, 2005 and the recently published results of Kohma et al (2019), which showed the maximum ε occurring just above tropopause primarily by the changes in the static stability (N) under nearly height-independent TKE around the tropopause. This is different from the current study of which the vertical profile of ε is determined primarily by L T that is generally larger where N is smaller, as will be shown in Figures 7b and 7c.…”
Section: 1029/2019jd030287contrasting
confidence: 99%
See 1 more Smart Citation
“…The strongest turbulence below the tropopause is also seen from individual profiles as well, which will be demonstrated in Figure 11a. The height of the maximum ε in the current study is different from some previous studies using radar data (e.g., Nastrom & Eaton, 1997, 2005 and the recently published results of Kohma et al (2019), which showed the maximum ε occurring just above tropopause primarily by the changes in the static stability (N) under nearly height-independent TKE around the tropopause. This is different from the current study of which the vertical profile of ε is determined primarily by L T that is generally larger where N is smaller, as will be shown in Figures 7b and 7c.…”
Section: 1029/2019jd030287contrasting
confidence: 99%
“…Several studies have compared the turbulence estimated from the Thorpe analysis with the turbulence derived from other methods. There have been studies comparing turbulence from radiosondes with turbulence from radar (Hoshino et al, 2016;Kantha & Hocking, 2011;Kohma et al, 2019;Li et al, 2016;Luce et al, 2014;Wilson et al, 2014). Schneider et al (2015) calculated turbulence from radiosondes and from an instrument called the Leibniz Institute of Turbulence Observations in the Stratosphere (LITOS), which had an 8-kHz sampling frequency and compared the two turbulence distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the direct solar point is passing through the tropical western Pacific from north to south at this time, a significant increase in turbulence activity may occur from July to September. Kohma et al [26] mentioned that seasonal variation in radar-based ε shows a broad maximum in August-October and low values in November-January in the lower stratosphere, which is similar to our results. The statistical characteristics of gravity waves at Gadank, which has the same latitude as Guam, are discussed in detail in [53][54][55], which have a certain reference significance for the turbulence distribution characteristics in this paper.…”
Section: Overview and Discussionsupporting
confidence: 93%
“…Nath et al used high-resolution GPS radio measurements over Gazanki in the tropics for nearly three years to investigate the characteristics of the seasonal variation and height distribution of various turbulence parameters [23]. Kohma et al estimated ε in the Antarctic region for a whole year and compared the results of radar data by using the Thorpe method [26]. Jian Zhang et al used high-resolution radiosonde data from 2012 to 2016 in mid-latitude regions to validate the credibility of Thorpe analysis in atmospheric turbulence studies [27].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, high degree of intermittency and spatial variability of turbulence occurring in the free atmosphere cannot be accounted by the single radiosonde profile. Other than this, the proportionality constant between Thorpe scale and Ozmidov scale, that is, c = L o /L T varies with altitude with values ranging from 0.3 to 1 at different altitudes (Kohma et al, 2019).…”
Section: Statistical Comparison Of Turbulence Parameters From Both Tementioning
confidence: 99%